Synthetic Coral Scaffold and Platelet Rich Plasma for Bone Remodelling after Tooth Extraction - Mahanani, Erlina Sih; Putri, Ferly Aulia; Rahma, Zalfa Kamila Siti; Salsabila, Rismananda Putri; Ramadhanti, Tamara Istna; Puspita, Sartika (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: The human body can self-repair. However, if the damage occurs excessively or reaches a critical defect, it requires material substitution to restore its shape and function. Tissue engineering is developed based on the principle of reconstructing damaged tissues due to critical defects to restore, maintain, and repair damaged tissues or organs by applying three main components: scaffolds, signaling molecules, and cells. This study aims to investigate the ability of synthetic coral scaffold incorporated with Platelet Rich Plasma in bone remodeling after tooth extraction. Method: This study was conducted as in vivo experimental laboratory study with a post-test control group design. The 48 male Rattus norvegicus rats were divided into 4 treatment groups. Firstly, the rats’ teeth were extracted, then, on the tooth extraction area, it was treated with povidone-iodine (control group), curaspon, scaffold only, and scaffold-incorporated Platelet Rich Plasma. Result: The results of the Kruskall-Wallis test showed no significant difference (p > 0.05) between the four treatment groups. articleConclusion: The PRP-incorporated synthetic coral scaffold had the highest score of collagen formation density and significantly accelerated collagen formation in the bone remodeling process compared to other treatment materials.